Extended halos and intracluster light using Planetary Nebulae as tracers in nearby clusters. Issue Volume 11:Issue A29B(2015) (27th October 2016) - Arnaboldi, Magda
Abstract: Since the first detection of intracluster planetary nebulae in 1996, imaging and spectroscopic surveys identified such stars to trace the radial extent and the kinematics of diffuse light in clusters. This topic of research is tightly linked with the studies of galaxy formation and evolution in dense environment, as the spatial distribution and kinematics of planetary nebulae in the outermost regions of galaxies and in the cluster cores is relevant for setting constraints on cosmological simulations. In this sense, extragalactic planetary nebulae play a very important role in the near-field cosmology, in order to measure the integrated mass as function of radius and the orbital distribution of stars in structures placed in the densest regions of the nearby universe.